Human capital, firm capabilities and productivity growth - Ilke Van Beveren; Stijn Vanormelingen (National Bank of Belgium, 2014)
This paper determines the relative importance of technical efficiency and reallocation for aggregate productivity growth in a small open European economy. To this end we use a dataset containing all Belgian firms active in the private sector, both services and manufacturing. We observe at the firm level a number of factors that have been shown to be drivers of productivity differences across firms. More precisely, we have information on human capital such as the level of education and the amount of on-the-job training received by the employees. Moreover we observe the international activities of the firms such as imports and exports. This allows us to make a careful analysis of the micro foundations of aggregate productivity growth by applying the decomposition introduced by Petrin and Levinsohn (2012). The outcome of this exercise will not only provide us with a better understanding of the slowdown of productivity growth in Europe over the past decades, but also give an indication on the role of different productivity drivers in this process.
Keywords: D24; O47; C23; 330; Productivity; Productivity Decomposition; Dienstleistungssektor; Industrie; Produktivität; Humankapital; Kleine offene Volkswirtschaft; Panel; Belgien